PENGARUH PENGGUNAAN ECU STANDAR DAN ECU JUKEN DENGAN VARIASI INJEKTOR TERHADAP TORSI DAN DAYA SEPEDA MOTOR YAMAHA V-IXION - Afwan, Muhammad Aulia; Rahardjo, Winarno Dwi (Automotive Science and Education Journal, 2020)
The resulting engine performance motorcycle injection less than the maximum. This is due to inadequate intake of fuel sprayed by the injector and injection duration short. This study aims to determine the effect of the use of a standard ECU and ECU juken with injector variation of the torque and power of motorcycle Yamaha V-Ixion. The study used a motorcycle Yamaha V-Ixion. The method used in this research is true experimental design and data analysis descriptive statistics. The results showed that the use of standard injector standard ECU obtain maximum torque of 13.2 Nm and 10.33 kW maximum power, while the injector racing produces the highest torque Nm 13.32 and 10.40 kW power. On the use of the ECU juken 14.06 Nm torque and power 11.02 kW while ECU juken racing injector of torque 14.31 Nm and 11.22 kW power. Based on test results, it can be concluded that the use of the ECU juken racing injector effect in increasing the torque and power of motorcycle injection